(untitled) (International Journal of Engineering and Computer Science, 2016)
Now a days power demand are increased to reduce the power demand using renewable the energy systems. With the increasing integration of renewable energy generation into high-power grids, transmission at the dc level is becoming increasingly more useful than ac transmission. In this regard, emerging application, such as offshore wind farms, require a high-power offshore wind energy systems. The proposed dc/dc converter is characterized by the resonant switching transitions to achieve minimum switching losses and maximum system efficiency. Therefore, a higher switching frequency is conceivable to attain a higher power density. The double stage output voltage of the proposed converter operates at seven times as high as the input voltages with a small device count. The output capacitors are charged and discharged continuously by a 180 phase shift with respect to each other to eliminate the output voltage ripples with low capacitance requirements.The proposed series-modular and cascade configurations show the intrinsic merits of being readily applicable to multistage power switching converter. The developed topology has been implemented on a 5-kw prototype converter to test its feasibility.